Practical guide to using the CDM Regulations 2015 : teamwork not paperwork - Putsman, Tony; McArthur, Paul (ICE Publishing, 2015)
Although the CDM Regulations first came into effect in 1995, there is still widespread misunderstanding regarding how project teams should perform in order to satisfy their legal obligations. Addressing the latest revisions to the CDM Regulations, 'Practical Guide to Using the CDM Regulations 2015' unpicks the common misunderstandings and provides clear examples of how the regulations can be applied to real-life cases.